Tamiflu, clinical trials and the Public Accounts Committee. Issue 11 (5th June 2014) - Chaplin, Steve
Abstract Steve Chaplin discusses the problem of getting access to data from unpublished trials, as highlighted in a report on the stockpiling of Tamiflu.